2019
DOI: 10.1021/acsomega.9b01200
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Small Gold Nanorods and Their Subsequent Functionalization with Hairpin Single Stranded DNA

Abstract: Small gold nanorods have a significantly large absorption/scattering ratio and are especially beneficial in exploiting photothermal effects, for example in photothermal therapy and remote drug release. This work systematically investigates the influence of growth conditions on the size, growth yield, and stability of small gold nanorods. The silver-assisted seed-mediated growth method was optimized to synthesize stable small gold nanorods with a high growth yield (>85%). Further study on the influence of silve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…We believe that the CTAB bilayer on NRs did not allow an effective ligand exchange reaction for the direct attachment of SH-(CH 2 ) 3 -ssDNA-X. Our observation is also supported by literature in which a ligand exchange of CTAB with a thiolated molecule, such as mercaptopropionic acid, was conducted before attachment of -ssDNA. However, to the best of our knowledge, no report is available presenting attachment of SH-(CH 2 ) 3 -ssDNA-X onto Au NRs via a direct ligand exchange reaction for biosensing applications. Nevertheless, our goal has been to develop a simplified biosensor for the microRNA assay without performing complicated ligand exchange chemistry to functionalize nanostructures.…”
Section: Results and Discussionsupporting
confidence: 76%
“…We believe that the CTAB bilayer on NRs did not allow an effective ligand exchange reaction for the direct attachment of SH-(CH 2 ) 3 -ssDNA-X. Our observation is also supported by literature in which a ligand exchange of CTAB with a thiolated molecule, such as mercaptopropionic acid, was conducted before attachment of -ssDNA. However, to the best of our knowledge, no report is available presenting attachment of SH-(CH 2 ) 3 -ssDNA-X onto Au NRs via a direct ligand exchange reaction for biosensing applications. Nevertheless, our goal has been to develop a simplified biosensor for the microRNA assay without performing complicated ligand exchange chemistry to functionalize nanostructures.…”
Section: Results and Discussionsupporting
confidence: 76%
“…Although the seedless synthesis method did not initially attract much attention, some researchers used the method to acquire products that are difficult to obtain by traditional seed-mediated growth methods, such as small-sized GNRs. However, a more advanced method is needed to synthesize ultrasmall GNRs, as traditional technology tends to increase the concentration of seeds added in the growth solution, which sacrifices both yield and monodispersity (Chang and Murphy 2018;Cheng et al, 2019;Mbalaha et al, 2019).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…The CTAB concentration is closely related to the yield, shape, and size of GNRs. Studies have shown that CTAB as a surfactant can prevent isotropic grain growth, thus preventing it from forming spherical by-products (Mbalaha et al, 2019). CTAB of different suppliers can lead to different synthesis results of GNRs (Scarabelli et al, 2015).…”
Section: Reduce Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The use of gold nanoparticles in nanoscience has generally depended on their ability to support strong localized surface plasmon resonances (LSPRs) and on the ease of modifications of their surfaces. The LSPR enhances electromagnetic fields in the vicinity of the metal surfaces, which in turn, can be used to enhance fluorescence, light scattering, photocatalytic process, and other properties of nearby molecules. , Gold nanorods (GNRs), in particular, have emerged as versatile platforms for these applications due to their tunable optical properties as well as their asymmetric shape, which support the generation of distinct transverse and longitudinal surface plasmon modes . In order for GNRs to be used as fluorescence/catalytic amplifiers, the molecules to be stimulated should ideally be near the GNR ends, where the strong longitudinal field greatly enhances their molecular or emission properties. However, anchoring molecules in this specific area requires site-specific functionalization of the GNR surface.…”
Section: Introductionmentioning
confidence: 99%